CHIVA to treat saphenous vein insufficiency in chronic venous disease: characteristics and results - Felipe Puricelli Faccini; Stefano Ermini; Claude Franceschi (Jornal Vascular Brasileiro, 2019)
Abstract There is considerable debate in the literature with relation to the best method to treat patients with chronic venous disease (CVD). CHIVA is an office-based treatment for varicose veins performed under local anesthesia. The aim of the technique is to lower transmural pressure in the superficial venous system and avoid destruction of veins. Recurrence of varicosities, nerve damage, bruising and suboptimal aesthetic results are common to all treatments for the disease. This paper evaluates and discusses the characteristics and results of the CHIVA technique. We conclude that CHIVA is a viable alternative to common procedures that is associated with less bruising, nerve damage, and recurrence than stripping saphenectomy. The main advantages are preservation of the saphenous vein, local anesthesia, low recurrence rates, low cost, low pain, and no nerve damage. The major disadvantages are the learning curve and the need to train the team in venous hemodynamics.